FAKTOR YANG MEMPENGARUHI KUALITAS PENGELOLAAN DAN ADMINISTRASI LAPORAN KEUANGAN DESA - Praptiningsih, Praptiningsih; Yetty, Fitri (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to determine the effect of the Utilization of Information Technology, Internal Control Systems, the influence of Financial Supervision, Competence of Human Resources, Regional Financial Accounting Systems to the Quality of Financial Statement Management and Administration. Design/methodology/approach- The sample in this study were employees of the Regional Government Work Unit (SKPD) of Pandeglang Regency with 50 respondents from 18 Regional Apparatus Organizations (OPD) of Pandeglang Regency. The data analysis technique used in this study is the multiple linear regression. Findings- The results of this study indicate that the Use of Information Technology and human resource competencies have a significant effect on the Quality of Management and Administration of Financial Statements. Implications- For SKPD Pandeglang regency it is recommended to improve financial supervision and internal control systems in presenting the quality of financial statement information on the management and administration of financial statements.Keywords: Quality, Management, Administration, Reports, and Finance